Sheikh Athiyah Saqr's Ijtihad Method on the Obligation of Husband to Fulfill Wife's Wishes When Craving - Aini, Nur; Azwar, Zainal (Minhaj: Jurnal Ilmu Syariah, 2025)
Support in a marital relationship is an obligation for a husband towards his wife and children. Fulfilling the wife's wishes when she has cravings is categorized as a husband's maintenance according to Sheikh Athiyah Saqr, which is also legally obligatory. However, seeing the phenomenon of excessive coveting from wives that often occurs nowadays, it is necessary to classify wives' desires, which the husband must fulfill by law. This research aims to analyze Sheikh Athiyah Saqr's method of ijtihad in his fatwa on the obligation for husbands to fulfill their wives' desires when they desire them and to relate the relevance to current phenomena. This research uses the library research method. The data collection technique used is library research. The data analysis technique used in this research is the descriptive method. The result of this research is that Sheikh Athiyar Saqr in determining this fatwa used the qiyas and maslahah murlah methods. According to Sheikh Athiyah Saqr, the obligation of a husband to fulfill his wife's wishes when she desires is translated into the obligation of the husband to provide his wife with daily living. Apart from that, fulfilling the wife's wishes by the husband is considered to bring benefits to the wife and the fetus. However, it is necessary to limit the wife's wishes which must be fulfilled by the husband, namely wishes that do not violate the Shari'a, do not bring harm, and are still within the limits of the husband's capabilities.